Penilaian Employee Performance Berbasis Job Satisfacation Pada Rumah Sakit Amal Sehat di Wonogiri - Fitri Madani; Mutamimah (Penerbit Jurnal Indonesia, 2026)
This study aimed to analyze the effect of Workload and Employee Engagement on Employee Performance with Job Satisfaction as a mediating variable among employees of Amal Sehat Hospital in Wonogiri. The research employed a quantitative explanatory approach with a sample of 200 respondents, representing the entire hospital workforce. Data were collected through a Likert-scale (1–5) questionnaire and analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) with SmartPLS software.The results indicated that both Workload and Employee Engagement have a positive and significant influence on Job Satisfaction and Employee Performance. Furthermore, Job Satisfaction was found to mediate the relationship between Workload and Employee Engagement with Employee Performance. This means that balanced workloads and higher employee engagement lead to greater job satisfaction, which in turn enhances performance. These findings provide valuable insights for the management of Amal Sehat Hospital in developing strategies to improve human resource performance through effective workload management, increased engagement, and strengthened job satisfaction.